Efficiency of S-genotyping for diversity screening and self-incompatible group identification of almond cultivars within the Mediterranean basin. Issue 3 (4th May 2021) - Gouta, Hassouna; Ksia, Elhem; Laaribi, Ibtissem; Bennici, Stefania; La Malfa, Stefano; Gentile, Alessandra; Distefano, Gaetano
ABSTRACT: Molecular tools were largely used to characterise native almond ( Prunus dulcis Mill.) cultivars, to elucidate their diversification and to establish their membership to Mediterranean germplasm pools. Hereby, the efficiency of the application of PCR techniques to study the genetic diversity of S alleles in almond was tested to identify self-incompatible cultivar combinations and groups. Hence, an analysis with consensus AS1II and AmyC5R and with allele-specific primers was performed for 25 almond accessions including 17 local Tunisian cultivars, 7 advanced selections, and 1 extra group from Italy in order to identify their S-genotype. Interestingly, all genotypes were assigned to their specific self-incompatible groups and a new group (LI) has been established. The two cultivars 'Dillou' and 'Porto' both considered as self-compatible have been demonstrated to be self-incompatible. Results reveal also a discrepancy for the S -genotype assigned to 'Zahaaf' preserved in the International almond collection. Thus, S genes genotyping of commercially used or newly released cultivars is very useful as we demonstrated that it may show that common knowledge may be partly inaccurate. For important varieties, this immediately has a consequence for cultivation practices, also for smallholder orchards as changing an incorrect practice may in time increase yield and also guarantee yield stability.